Peran Orang Tua dalam Pendampingan Pembelajaran Tatap Muka Terbatas Siswa Madrasah Ibtidaiyah - Widiyanti, Remita; Rouzi, Kana Safrina; Ardiyaningrum, Martalia; Badriah, Laelatul; Afifah, Ni’mah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The reopening of schools requires the willingness of parents who have the primary responsibility in the education of their children. This study aims to determine the role of parents in limited face-to-face learning assistance and the supporting and inhibiting factors in limited face-to-face learning assistance for Grade V students of MI YAPPI Tanjung Getas Playen Gunungkidul. This research adopts a qualitative descriptive approach. The subjects of this study were parents of grade V, students of grade V, guardians of grade V, and the principal of MI YAPPI Tanjung Madrasah. Data collection in this study was through observation, interview and documentation. Data validity techniques using source triangulation. Data analysis techniques include data collection, data reduction, data presentation, and conclusion. Based on the results of the study, parents of Grade V MI YAPPI Tanjung support limited face-to-face learning, starting from before the implementation, implementation, and after the implementation of limited limited face-to-face learning. This is evidenced by parents 1) nurturing, 2) accompanying, 3) motivating, 4) facilitating, 5) fostering children's creativity, 6) supervising children, 7) shaping character, and 8) increasing religious values.